Islam sebagai Agama Damai dan Toleran: Studi Penafsiran Al-Qur’an Surat Al-Mumtahanah Ayat 7-9 - Zahid, Reza Ahmad; Abidin, Muhammad Zainal; Mukhlison, Moch. (Kartika: Jurnal Studi Keislaman, 2024)
This study analyzes the Islamic stance towards non-Muslims regarding tolerance and peace, focusing on the interpretation of Surah al-Mumtahanah verses 7-9. The research is motivated by academic concerns over the frequent misconceptions that view religion as a source of violence, particularly in interfaith relations. This study uses a qualitative approach with a literature review. This study found that Islam teaches two main principles in interacting with non-Muslims: al-Birr (doing good) and al-Iqsath (being just). These values are embodied in verses that emphasize the importance of being kind and just towards non-Muslims who do not oppose Islam in social, legal, and economic aspects. This research indicates that Islam, in its normative teachings, promotes peace and tolerance, allows for harmonious interactions between different religious communities, and maintains the belief that Islam is the true faith. This study contributes to clarifying Islam's position towards non-Muslims in a broader context.